Sistema de información para el control, seguimiento y mantenimiento del equipamiento hospitalario - Chávez Gómez, Víctor Hugo (2010)
The main purpose of this research is to present a solution that enable to manage efficient and reliable way, all of the information in relation to control, tracking and the hospital equipment maintenance. So, was taken as an object of study of Engineering Department of the Central Hospital of the Air Force of Peru, which presents a lot of administrative deficiencies character in its internal processes of reception, record and closing of Work Orders as well as the preventive and corrective maintenance of the hospital equipment of the HCFAP.The contemplated solution comprises from analysis and design to the development of some use cases more significant of the application.